The importance of advanced glycation end products, lipid and redox biomarkers determination in patients with diabetes mellitus - Vujčić, Sanja; Kotur-Stevuljević, Jelena; Beljić Živković, Teodora; Mišić, Milan; Mihajlović, Marija; Erceg, Sanja; Zeljković, Aleksandra; Koprivica-Uzelac, Branka; Perović Blagojević, Iva; Vekić, Jelena (Archives of Pharmacy, 2022)
Non-enzymatic glycation, oxidative stress (OS) and dyslipidemia are the main metabolic alterations behind the development of macrovascular complications (cardiovascular diseases) of diabetes mellitus (DM). However, clinical relevance of biomarkers of these processes in patients with microvascular complications (nephropathy, neuropathy, retinopathy) is less understood. Therefore, the aim of this study was to examine advanced glycation products (AGEs), biomarkers of OS, and dyslipidemia in 100 DM patients (33 without microvascular complications and 77 with complications) and 30 subjects without DM. AGEs levels were higher in patients with complications than in those without complications (median: 5.72; interquartile range: 4.60-6.54 U/mL vs. median: 4.84; interquartile range: 4.10-5.40 U/L; P